Reusable software components framework. - Al-Badareen, Anas Bassam; Selamat, Mohd. Hasan; A. Jabar, Marzanah; Din, Jamilah; Turaev, Sherzod (2010)
The concept of reusability is widely used, in order to reduce cost, effort, and time of software development. Reusability also increases the productivity, maintainability, portability, and reliability of the software products, which it has been evaluated before in other software products. The problems faced in software engineering not a lack of reuse, but a lack of widespread, systematic reuse. They know how to do it, but they do it informally. Therefore, strong attention must be given to this concept. This study aims to propose a systematic way of software reuse: build-for-reuse and buildby- reuse. The evaluation criteria of the reusable components are then adopted. Finally, the proposed framework is applied on C-Registration System.